PERUBAHAN TEKANAN DARAH PADA LANSIA YANG MELAKUKAN SENAM PROLANIS DI PUSKESMAS TAMALANREA KOTA MAKASSAR - Noyumala; Sri Darmawan; Sriwahyuni; Adalina Seltit (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Background: The high prevalence of hypertension sufferers worldwide is increasing in developed and developing countries, including Indonesia. Hypertension exercise is a sport that can relax blood vessels. Methods: Experimental quasi-research design with time series or pre and post designs. Population of 11 and using total sampling, Results: based on observations made at meetings I, III, V obtained the results of the comparison of systolic blood pressure before prolanis training p = 0.002 <a = 0.05 while the ratio of diastolic blood pressure after prolanis exercise p = 0.002 <a = 0.05. Conclusion: There were changes in systolic and diastolic blood pressure in hypertensive elderly after and before doing prolanic exercise. It is hoped that people with hypertension can exercise regularly because it can help lower blood pressure, improve fitness and increase the body's metabolism which can control blood pressure